Relationship between functional movement screen and athletic performance - Parchmann, C.; McBridge, J. M. (The Journal of Strength and Conditioning Research, 2011)
Tests such as the functional movement screen (FMS) and maximal strength (repetition maximum strength [1RM]) have been theorized to assist in predicting athletic performance capabilities. Some data exist concerning 1RM and athletic performance, but very limited data exist concerning the potential ability of FMS to assess athletic performance. The purpose of this investigation was to determine if FMS scores or 1RM is related to athletic performance, specifically in Division I golfers in terms of sprint times, vertical jump (VJ) height, agility T-test times, and club head velocity. Twenty-five National Collegiate Athletic Association Division I golfers (15 men, age = 20.0 ± 1.2 years, height = 176.8 ± 5.6 cm, body mass = 76.5 ± 13.4 kg, squat 1RM = 97.1 ± 21.0 kg) (10 women, age = 20.5 ± 0.8 years, height = 167.0 ± 5.6 cm, body mass = 70.7 ± 21.5 kg, squat 1RM = 50.3 ± 16.6) performed an FMS, 1RM testing, and field tests common in assessing athletic performance. Athletic performance tests included 10- and 20-m sprint time, VJ height, agility T-test time, and club head velocity. Strength testing included a 1RM back squat. Data for 1RM testing were normalized to body mass for comparisons. Correlations were determined between FMS, 1RMs, and athletic performance tests using Pearson product correlation coefficients (p <= 0.05). No significant correlations existed between FMS and 10-m sprint time (r = -0.136), 20-m sprint time (r = -0.107), VJ height (r = 0.249), agility T-test time (r = -0.146), and club head velocity (r = -0.064). The 1RM in the squat was significantly correlated to 10-m sprint time (r = -0.812), 20-m sprint time (r = -0.872), VJ height (r = 0.869), agility T-test time (r = -0.758), and club head velocity (r = 0.805). The lack of relationship suggests that FMS is not an adequate field test and does not relate to any aspect of athletic performance. Based on the data from this investigation, 1RM squat strength appears to be a good indicator of athletic performance